2017
DOI: 10.3390/rs9030280
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Maritime Target Detection Method for Optical Remote Sensing Imagery

Abstract: Maritime target detection from optical remote sensing images plays an important role in related military and civil applications and its weakness lies in its compromised performance under complex uncertain conditions. In this paper, a novel hierarchical ship detection method is proposed to overcome this issue. In the ship detection stage, based on Entropy information, we construct a combined saliency model with self-adaptive weights to prescreen ship candidates from across the entire maritime domain. To charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…A relatively large fraction of the authors (35%) used Google Earth images as the direct input data source in their research on vessel detection – either as exported data or simply as a print screen –, or as a source for collecting the greater amount of test data for machine learning methods (An et al, 2013, p. 201; Deng et al, 2013, Dong et al, 2013, Gan et al, 2015, Guo et al, 2015, Han et al, 2014, Hong et al, 2007, Huang et al, 2016, Johansson, 2011, Ju, 2015, Ma et al, 2010, p. 201; Shi et al, 2014, Xu et al, 2017, Xu et al, 2011, p. 201; Xu and Liu, 2016, Xu et al, 2014, Yang et al, 2017, Yang et al, 2014, You and Li, 2011, Zhang et al, 2016, Zou and Shi, 2016). One author has used data from Microsoft Virtual Earth (Yin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A relatively large fraction of the authors (35%) used Google Earth images as the direct input data source in their research on vessel detection – either as exported data or simply as a print screen –, or as a source for collecting the greater amount of test data for machine learning methods (An et al, 2013, p. 201; Deng et al, 2013, Dong et al, 2013, Gan et al, 2015, Guo et al, 2015, Han et al, 2014, Hong et al, 2007, Huang et al, 2016, Johansson, 2011, Ju, 2015, Ma et al, 2010, p. 201; Shi et al, 2014, Xu et al, 2017, Xu et al, 2011, p. 201; Xu and Liu, 2016, Xu et al, 2014, Yang et al, 2017, Yang et al, 2014, You and Li, 2011, Zhang et al, 2016, Zou and Shi, 2016). One author has used data from Microsoft Virtual Earth (Yin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…As seen in Table 2, around half of the vessel detection methods indicated that their input is only the PAN band, neglecting the MS data, and thus relying more on spatially oriented and less on spectral techniques (35 authors or 52%: Fernandez Arguedas, 2015, Bi et al, 2012, Buck et al, 2007, Corbane et al, 2010, Corbane et al, 2008, Corbane et al, 2008, Guang et al, 2011, Guo and Zhu, 2012, Harvey et al, 2010, Huang et al, 2011, Hung, 2016, Jin and Zhang, 2015, Jubelin and Khenchaf, 2014, Li et al, 2016, Li et al, 2016, Liu et al, 2014, Pan et al, 2015, Proia and Page, 2010, Qi et al, 2015, Shi et al, 2014, Tang et al, 2015, Wang et al, 2005, Willhauck et al, 2005, Xu et al, 2017, Xu and Liu, 2016, Yang et al, 2014, Yang et al, 2015, Yang et al, 2017, Yao et al, 2016, Yokoya and Iwasaki, 2015, Zou and Shi, 2016). On the other hand, 30% (20 authors) use only MS data, and 18% (12 authors) use both PAN and MS data (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework is similar to the two stages in [36]. However, the extraction and discrimination features are different from there.…”
Section: Introductionmentioning
confidence: 95%
“…They are very time-consuming because global searching is an indispensable part in the processing. Moreover, with the rapid development of remote sensing technology, the resolution of remote sensing images increases, and the intensity, structure, shape and texture information are more abundant [5][6][7][8]. Due to the irregular shape, unfixed size and other characteristics of ROIs, the extraction accuracy cannot be guaranteed when Aggregating neighboring pixels into superpixels can not only reduce the complexity of subsequent processing but also maintain the boundary information.…”
Section: Introductionmentioning
confidence: 99%